Pendidikan Spiritual Menurut Said Hawwa dan Relevansinya dalam Pendidikan Agama Islam di Indonesia - Susanti, Salamah Eka (Lembaga Yasin AlSys, 2024)
Spiritual education is education related to the formation of attitudes, mentality, inner self, emotions, and spiritual connection to a particular matter, aimed at achieving inner purity and spiritual intelligence in relation to drawing closer to Allah SWT. The presence of spiritual education serves to remove and cleanse the heart from ailments that people often experience when undergoing education in daily life. The purpose of this thesis is to understand the values of spiritual education and their relevance in daily life, as well as their application in the educational domain. The type of research used in this study is qualitative, utilizing the library research method, which involves collecting data or academic writings related to the research subject or gathering library-based data. The findings of this study indicate that spiritual education serves as a foundation for shaping a personality and mentality expected to provide enlightenment and a spiritual attitude to students. This is connected to the spiritual attitude of individuals as they navigate life. Spiritual education strives to nurture the human soul through tranquility of heart, inner enlightenment, and clarity of attitude, ultimately creating individuals with a strong, balanced inner and outer self.